Delimiting the Donor: The Dead Donor Rule - Robertson, John A. (The Hastings Center report, 1999)
The scarcity of vital organs has prompted several calls to either modify the dead donor rule or interpret it more broadly. Given its symbolic importance, however, the rule should be changed only cautiously.